Diet-Induced Gene Expression Changes of Cachectic Muscle, Adipose, and Liver. (14th June 2022) - Angelotti, Austin; Cole, Rachel; Webb, Amy; Pietrzak, Maciej; Belury, Martha
Abstract: Objectives: Cancer cachexia is a systemic disease characterized by muscle and adipose loss that cannot be reversed by increasing caloric intake. Our previous research has shown insulin resistance precedes cancer cachexia in the C26 mouse model of cachexia, and a diet high in linoleic acid, the essential omega-6 polyunsaturated fatty acid, attenuates the C26-induced insulin resistance. Therefore, to better understand how dietary linoleic acid is improving insulin sensitivity, we characterized gene expression changes in three major tissues responsible for controlling insulin sensitivity: skeletal muscle, adipose, and liver. Methods: Male CD2F1 (Charles River, MA) were randomized to semi-purified diet (24% fat by weight) containing fat prominently from lard, or containing fat prominently from safflower oil (a linoleic acid-rich oil). One week after diet randomization, mice were inoculated with colon-26 (C26) adenocarcinoma cells (1.0E6 cells). 13 days after inoculation mice were euthanized and gastrocnemius skeletal muscle, epididymal white adipose tissue, and liver tissue were collected for total transcriptome analysis using poly-A enriched next generation RNA-sequencing. Differentially expressed genes were selected based on p -values < 0.05. Results: There were no detectable differences in body weight or food intake between the two diets in mice with C26 tumors. Between the two diets 12 genes were differentially expressed in the muscle, while 57 genes were differentially expressed in the liver, and 314 genes were differentially expressed in adipose. Conclusions: A linoleic acid enriched diet had little effect on the skeletal muscle transcriptome but induced larger transcriptome changes in liver and adipose. This could suggest dietary linoleic acid increases insulin sensitivity through affecting metabolism in adipose and liver, rather than skeletal muscle. Determining these diet-induced transcriptome changes allows us to better target tissue-specific molecular mechanisms of linoleic acid in future research. Funding Sources: This work was supported by the Pelotonia Fellowship Program, the Ohio State University Comprehensive Cancer Center, and the National Institutes of Health.